TARIXIY TARAQQIYOTDA ETNONIMLARNING TRANSFORMATSIYALASHUV JARAYONLARI - Nazarov, N.A. (SCIENCE and SOCIETY, 2022)
The article examines the connection between the ethnonym Sire, reflected in the Orkhon inscription, which is an example of the Turkic runology with the hydronym of the Syr Darya. It is studied that the medieval Kipchaks, who played an important role in the ethnogenesis of the Turkic peoples, depicted as sirs in the Orkhon monument, played an important role in the Syr Darya basin in the early Middle Ages and the Middle Ages, since thanks to the Sirs-Kipchaks, the name of the Syr Darya river also entered the lexicon of the peoples of the region.
Keywords: Orkhon inscriptions; Sirs; Kipchaks; Seyanto; Tele; anciyent Turks; tribe; Syr Darya; ethnonym; hydronym; historical development